The Cytokine GM-CSF Drives the Inflammatory Signature of CCR2+ Monocytes and Licenses Autoimmunity - Croxford, Andrew L; Lanzinger, Margit; Hartmann, Felix J; Schreiner, Bettina; Mair, Florian; Pelczar, Pawel; Clausen, Björn E; Jung, Steffen; Greter, Melanie; Becher, Burkhard (Immunity (Cambridge, Mass.), 2015)
Granulocyte-macrophage colony-stimulating factor (GM-CSF) has emerged as a crucial cytokine produced by auto-reactive T helper (Th) cells that initiate tissue inflammation. Multiple cell types can sense GM-CSF, but the identity of the pathogenic GM-CSF-responsive cells is unclear. By using conditional gene targeting, we systematically deleted the GM-CSF receptor (Csf2rb) in specific subpopulations throughout the myeloid lineages. Experimental autoimmune encephalomyelitis (EAE) progressed normally when either classical dendritic cells (cDCs) or neutrophils lacked GM-CSF responsiveness. The development of tissue-invading monocyte-derived dendritic cells (moDCs) was also unperturbed upon Csf2rb deletion. Instead, deletion of Csf2rb in CCR2(+)Ly6C(hi) monocytes phenocopied the EAE resistance seen in complete Csf2rb-deficient mice. High-dimensional analysis of tissue-infiltrating moDCs revealed that GM-CSF initiates a combination of inflammatory mechanisms. These results indicate that GM-CSF signaling controls a pathogenic expression signature in CCR2(+)Ly6C(hi) monocytes and their progeny, which was essential for tissue damage.